1999
DOI: 10.3109/10826089909029390
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Acculturation, and Alcohol Consumption among Mexican Americans

Abstract: Studies of drinking patterns and related problems need to consider these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 16 publications
3
48
1
Order By: Relevance
“…Other studies have shown that there are different social norms concerning alcohol use among men and women in Mexico and the U.S. Drinking among males is acceptable in both contexts, while the low proportions of drinkers among foreign-born Mexican American females in the U.S. may reflect socialization in Mexico where there are sanctions against among women consuming alcohol (Alaniz et al, 1999). Studies have also found that women who immigrated to the U.S. in childhood consume more alcohol than women who immigrated to the U.S. as adults (Heilemann et al, 2002) and as Mexican American women acculturate and achieve higher status positions in the work force they use alcohol more and believe there are positive consequences to its use (Gilbert et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that there are different social norms concerning alcohol use among men and women in Mexico and the U.S. Drinking among males is acceptable in both contexts, while the low proportions of drinkers among foreign-born Mexican American females in the U.S. may reflect socialization in Mexico where there are sanctions against among women consuming alcohol (Alaniz et al, 1999). Studies have also found that women who immigrated to the U.S. in childhood consume more alcohol than women who immigrated to the U.S. as adults (Heilemann et al, 2002) and as Mexican American women acculturate and achieve higher status positions in the work force they use alcohol more and believe there are positive consequences to its use (Gilbert et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that marriage reinforces traditional Mexican values about motherhood and women's roles. Smoking and drinking are relatively common behaviors among men in Mexico, but very uncommon among women (Alaniz, Treno, & Saltz, 1999). A husband's cultural beliefs may have a stronger effect on his wife's pregnancy behaviors than his social support.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation has been examined increasingly as one of the factors accounting for American women (Alaniz, Treno, & Saltz, 1999). Among Korean Americans, high acculturation is related to higher body weight and light physical activity (Lee, Sobal, & Frongillo, 2000).…”
Section: Relationship To Breast Self-examination Frequencymentioning
confidence: 99%